Experimentally confirmed toltrazuril resistance in a field isolate of Cystoisospora suis - Aruna Shrestha; Barbara Freudenschuss; Rutger Jansen; Barbara Hinney; Bärbel Ruttkowski; Anja Joachim (Parasites & Vectors, 2017)
Abstract Background Constant treatment regimens with toltrazuril against Cystoisospora suis infection in piglets are being applied in the intensive production systems for the last two decades, but the possibility of resistance development has not been addressed so far despite limited availability of treatment alternatives. Recently, a pig producer in The Netherlands who routinely used toltrazuril complained about diarrhea in suckling piglets in the absence of bacterial and viral pathogens, and oocysts of C. suis could be isolated from feces of affected litters. Methods Piglets from two litters were infected with a field isolate of C. suis, Holland-I, and treated with 0 (Holl-Ctrl), 20 (Holl-20) or 30 (Holl-30) mg/kg of body weight (BW) of toltrazuril (Baycox®). The efficacy of toltrazuril was measured by assessment of oocyst excretion, fecal consistency and BW gain. A separate litter was infected with a toltrazuril-susceptible strain of C. suis, Wien-I, and treated with 0 (Wien-Ctrl) or 20 (Wien-20) mg/kg BW of toltrazuril for comparison. Results Treatment with the recommended (20 mg/kg) dose of toltrazuril completely suppressed oocyst shedding and diarrhea in group Wien-20. The prevalence of oocyst excretion was 100% in the groups infected with Holland-I and 80% in the group Wien-Ctrl. Most days with diarrhea were observed in group Holl-20 with an average of 6.40%, followed by 5.71% in Wien-Ctrl, while in Holl-Ctrl and Holl-30 diarrhea was only seen in 1.79% of the samples (n = 14/piglet). Oocyst excretion, fecal consistency and BW gain did not differ significantly among groups infected with Holland-I, indicating loss of efficacy to toltrazuril. Conclusion Experimental infections and treatment confirmed toltrazuril resistance against the field isolate even at increased dosage. Such isolates are a potential threat to pig production as no other effective and economically sustainable alternative treatment is currently available. In the absence of a standardized protocol for resistance testing in C. suis, regular parasitological examination and, if possible, experimental confirmation should be considered to evaluate the extent and consequences of toltrazuril resistance.